Bacteriological Analysis of Raw Beef Retailed in Selected Open Markets in Accra, Ghana - Michael Olu-Taiwo; Prince Obeng; Akua Obeng Forson (Journal of Food Quality)
Beef is an important and popular source of protein and nutrients. Constant monitoring and evaluation of the microbiological contamination is pertinent for its safety and quality. This study aimed to assess the bacteriological profiles and the bacterial loads in beef, as well as investigate food safety practices among beef retailers in selected open markets in Accra, Ghana. This was a cross-sectional study with beef samples randomly purchased from six selected open markets in Accra metropolis. Beef samples were examined for total aerobic count (TAC) and total coliform count (TCC). Bacterial identification was performed by standard bacteriological methods and a well-structured questionnaire was administered to assess food safety and hygienic practices of beef retailers. Overall, mean TACs ranged between 2.2 × 103 and 1.3 × 104 CFU/g, while mean TCCs ranged between 1.9 × 102 and 7.4 × 102 CFU/g. Beef samples were mostly contaminated with Staphylococcus spp. (34%), Klebsiella oxytoca (17%), Enterobacter spp. (15%), and Proteus vulgaris (3%). This study showed varying levels of bacterial contamination of retailed beef sold in different Accra markets. According to the Health Protection Agency guidelines for assessing microbiological safety of ready-to-eat foods, our mean TACs were satisfactory, while mean TCCs were within borderline quality. The results of this study revealed that the majority of beef vended in open markets in Accra is contaminated with coliform and pathogenic bacteria. Therefore, more training in safe food handling and good hygiene practices is required for beef retailers. Conclusively, effective monitoring of the bacteriological profiles and bacterial loads of meat and meat products in abattoirs and points of sale should be established, since such a continuous monitoring system could help prevent potential health problems for consumers and provide information on possible sources of meat borne intoxication and infection.